Impacts of tillage operations and microirrigation practices on weed infestation of BRRI Dhan 28 - Khatun, S; Ahmed, SU; Faiz, SMA; Rahmana, AHM Mustafizur (Dhaka University Journal of Biological Sciences, 2015)
An experiment was conducted with BRRI dhan 28 following four irrigation treatments (flood, drip, alternate wetting and drying, sprinkler) and two tillage methods (conventional or puddled and unpuddled). Highest number of weed infestation over conventional tillage was observed when herbicide was not applied. Weed biomass was recorded maximum in sprinkler irrigation followed by alternate wetting and drying (AWD) and flood irrigation. The main type of weed in the rice field was sedges. Weed infestation at 20 and 40 days after herbicide application was found to be the highest due to sprinkler irrigation over AWD and flood irrigations. Unpuddled tillage showed lower weed number and biomass over the conventional puddle tillage. Dhaka Univ. J. Biol. Sci. 24(2): 131-136, 2015 (July)